1987
DOI: 10.1111/j.1439-0396.1987.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid, glutathione metabolism, and electrical conductivity in bovine mastitic udder tissue

Abstract: Zusammenfassung Sialinsäure‐, Glutathion‐Stoffwechsel und elektrische Leitfähigkeit im Eutergewebe von an Mastitis erkrankten Kühen Es wurden Sialinsäure, Glutathion (GSH), Glutathion‐Peroxidase (GSH‐Px), Gammaglutamin‐Transferase (γ‐GT), Aspartat‐Aminotransferase (ASAT), Na, K und die elektrische Leitfähigkeit im Eutergewebe von an Mastitis erkrankten Kühen im Vergleich zu gesunden Kühen bestimmt. Die gemessenen Parameter im gesunden bzw. erkrankten Eutergewebe betrugen für Sialinsäure 0,4 bzw. 1,0 mM/L (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Generally, our study shows together with our earlier reports (Ali‐Vehmas et al., 1997; Malbe et al., 2003) that selenium may contribute to the protection of mammary gland from invading bacteria. Free radical generation and oxidative injury are thought to be important mechanisms contributing to morbidity, including mastitis (Atroshi et al., 1987, 1989, 2000). However, the mechanism by which the release of O 2 results in bactericidal effects is poorly understood, but is generally held to be related to the further generation of more reactive radical species, such as OH • , singlet oxygen and hypochlorite or hypothiocyanate (Del Maestro, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, our study shows together with our earlier reports (Ali‐Vehmas et al., 1997; Malbe et al., 2003) that selenium may contribute to the protection of mammary gland from invading bacteria. Free radical generation and oxidative injury are thought to be important mechanisms contributing to morbidity, including mastitis (Atroshi et al., 1987, 1989, 2000). However, the mechanism by which the release of O 2 results in bactericidal effects is poorly understood, but is generally held to be related to the further generation of more reactive radical species, such as OH • , singlet oxygen and hypochlorite or hypothiocyanate (Del Maestro, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in dairy cows have shown that selenium deficiency is associated with nutritional muscular dystrophy, cystic ovaries, retained placental membranes, metritis and infertility (Jukola et al., 1996; Hemingway, 2003). Other studies have shown evidence that selenium deficiency is associated with increased prevalence to intramammary infections (Smith et al., 1984, 1997; Atroshi et al., 1987, 1989; Erskine et al., 1989, 1990; Malbe et al., 1995; Ryan, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Much less information is available from studies carried out using dietary antioxidants and mycotoxins (Rizzo et al 1994;Abel & Gelderblom, 1998;Yin et al 1998;Belmadani et al 1999;Galvano et al 2001;Gautier et al 2001). The protective properties of antioxidants probably result from their ability to act as superoxide anion scavengers, thereby protecting cell membranes from mycotoxin-induced damage; in some cases, antioxidant vitamins may play a role in preventing mycotoxicosis (Atroshi et al 1987).…”
mentioning
confidence: 99%
“…Therefore we suggested that the increase of this enzyme activity in the inflammed tissue would represent a defence against the oxygen free radicals formed during peroxidation of arachidonic acid-like lipids, and be at the same time responsible for the markedly increased formation of PGEs in inflammation (ATROSHI et al, 1987b). Yet another GSH-enzyme, cytochrome P-450 was also increased in the mastitic udder tissue (ATROSHI et al, 1987~).…”
Section: Discussionmentioning
confidence: 90%
“…':-:' P < 0.01. The original values for the various biochemical traits can be found elsewhere(ATROSHI et al, 1987).…”
mentioning
confidence: 99%